Higher Market Thickness Reduces Matching Rate in Online Platforms: Evidence from a Quasiexperiment - Li, Jun; Netessine, Serguei (Management Science, 2020)
Market thickness is a key parameter that can make or break a platform’s business model. Thicker markets can offer more opportunities for participants to meet and higher chances that a potential match exists. However, they can also be vulnerable to potential search frictions. In this paper, using data from an online peer-to-peer holiday property rental platform, we aim to identify and measure the causal impact of market thickness on matching rates. In particular, we exploit an exogenous shock to market size caused by a one-time migration of listings from other platforms, which gives rise to a quasiexperimental design. We find that increased market thickness actually leads to lower matching rates. Keeping search technology and other factors constant, doubling market size leads to a 15.4% reduction in traveler confirmation rate and a 15.9% reduction in host occupancy rate. As a result, the platform lost 5.6% of potential matches because of the increased market size. We attribute the effect to increased search friction: travelers’ search intensity increases by 18.3% when market size doubles. This effect is especially prominent when the matching needs to take place within a limited time. Our results offer insights for future empirical and theoretical research on matching markets. They also highlight that is important for platform owners to watch out for increased search frictions as markets grow and invest in search technologies to facilitate more efficient search. This paper was accepted by Charles Corbett, operations management.